New York in Salman Rushdie’s Fury - Acharya, Pushpa Raj (Literary Studies, 2016)
Postcolonial and diasporic novels, such as Salman Rushdie's Fury, explore the interconnections between the global cities and human mobility. Bodily as well as other physical rhythms create affects, which in turn shape rhythm of the urban spaces. New York in such fictional works appears as an exploding, spasmodic city that renews itself with renovations and destruction.